Introducing Nietzsche - Gane, Laurence; Chan, Kitty (Cambridge : Icon Books, 1998)
Text and cartoon illustrations introduce the philosophy of Friedrich Nietzsche, with information on key events in the nineteenth-century German thinker's life.
Includes bibliographical references (p. 174-175).
Adult.
Adult
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Philosophy, German -- 19th century; German philosophy; Philosophy